Sudden unexpected death in epilepsy: Identifying risk and preventing mortality. (23rd October 2015) - Lhatoo, Samden; Noebels, Jeffrey; Whittemore, Vicky; ,
Summary: Premature death among individuals with epilepsy is higher than in the general population, and sudden unexpected death is the most common cause of this mortality. A new multisite collaborative research consortium, the Center for sudden unexpected death in epilepsy (SUDEP) Research (CSR), has received major funding from the National Institutes of Health (NIH) to examine the possible biologic mechanisms underlying this potentially preventable comorbidity and develop predictive biomarkers for interventions that could lower SUDEP incidence. This inaugural report describes the structure of the CSR, its priorities for human and experimental research, and the strategic collaborations and advanced tools under development to reduce this catastrophic outcome of epilepsy. The CSR Partners Program will work closely with committed volunteer agencies, industry, and academic institutions to accelerate and communicate these advances to the professional and lay community.